2019
DOI: 10.1088/1361-6560/ab489f
|View full text |Cite
|
Sign up to set email alerts
|

A multi-organ cancer study of the classification performance using 2D and 3D image features in radiomics analysis

Abstract: The purpose of this study was to investigate the predictive performance of 2D and 3D image features across multi-organ cancers using multi-modality images in radiomics studies.In this retrospective study, we included 619 patients with three different cancer types (intrahepatic cholangiocarcinoma (ICC), high-grade osteosarcoma (HOS), pancreatic neuroendocrine tumors (pNETs)) and four clinical end points (early recurrence (ER), lymph node metastasis (LNM), 5-year survival and histologic grade). The image feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 44 publications
0
42
0
Order By: Relevance
“…They showed that the same radiomics model was effective for predicting survival in two organs, but the results could be invalid because their feature selection approach was biased [20]. Another study attempted to explore the feasibility of applying the same set of radiomics features [21]. However, the goal was not to find common features but to compare the performance of 2D and 3D radiomics in intrahepatic cholangiocarcinoma, osteosarcoma, and pancreatic neuroendocrine tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…They showed that the same radiomics model was effective for predicting survival in two organs, but the results could be invalid because their feature selection approach was biased [20]. Another study attempted to explore the feasibility of applying the same set of radiomics features [21]. However, the goal was not to find common features but to compare the performance of 2D and 3D radiomics in intrahepatic cholangiocarcinoma, osteosarcoma, and pancreatic neuroendocrine tumors.…”
Section: Discussionmentioning
confidence: 99%
“…This is because tumors in different organs might share common properties. Thus, there is a scientific curiosity in applying radiomics features found in a given organ to other tumors in different organs [20,21]. A seminal study by Aerts et al explored the application of the same radiomics features to two different organs, but this topic was not their primary aim and was thus insufficiently explored.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could provide a stronger characterization compared to simply performing the analysis on a single 2D patch collected from each mass, as often performed in 2D radiomic analyses. 67 To test this latter hypothesis, the final radiomic model was used to reclassify the test set masses based only on the signatures extracted from a single patch (coronal view), resulting in a significantly lower performance (AUC = 0.84 vs 0.90). Nevertheless, a fully 3D radiomic approach should also be investigated in future, to allow for the evaluation, with larger image datasets, of the potential advantage of a fully 3D radiomic signature over the current 2D approach.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it should be noted that the proposed approach, although performed on a 2D basis, did take advantage of the 3D nature of the images, since superimposition of tissue was still avoided, and the final radiomic score for each mass was obtained by combining different signatures extracted over multiple angles. This could provide a stronger characterization compared to simply performing the analysis on a single 2D patch collected from each mass, as often performed in 2D radiomic analyses 67 . To test this latter hypothesis, the final radiomic model was used to reclassify the test set masses based only on the signatures extracted from a single patch (coronal view), resulting in a significantly lower performance (AUC = 0.84 vs 0.90).…”
Section: Discussionmentioning
confidence: 99%